2008
DOI: 10.4103/0971-4065.45291
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy related acute kidney injury: A single center experience from the Kashmir Valley

Abstract: All patients admitted with pregnancy related acute renal failure (PRAKI) from June 2005 to May 2007 were studied with respect to etiology, clinical features, and outcome of PRAKI. Of 569 cases of acute kidney injury (AKI), 40 (7.02%) cases were related to gestational problems; the age of the patients ranged from 15 to 45 years. Septic abortion was the most common cause of PRAKI, accounting for 20 (50%) cases of which 15 (75%) cases occurred in the first and five (25%) in the second trimester. Other causes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 9 publications
6
63
3
4
Order By: Relevance
“…10,11 There was one (6.6%) maternal mortality in our study compared to 2.7% in the Moroccan study and 20% in the study by Najar et al 10,11 …”
contrasting
confidence: 39%
“…10,11 There was one (6.6%) maternal mortality in our study compared to 2.7% in the Moroccan study and 20% in the study by Najar et al 10,11 …”
contrasting
confidence: 39%
“…The identification of risk factors associated with AKI and its poor prognosis is required so that preventive and early diagnosis measures can be taken, aiming to reduce patients' mortality. Our findings were supported by Najar et al [38] who reported 15% who had KI was associated with preeclampsia and (12%) in Ansari et al [39] While a study of Gurrieri et al [17] observed that kidney injury was associated with preeclampsia in a substantial percentage (20.4 %) of patients as well. On the contrary, Hachim et al [40], Erdemoglu et al [41] and Arrayhani et al [31], Said et al, [42] and Suraj et al [43] found that pre-eclampsia/eclampsia was (33.3%).…”
Section: Discussionsupporting
confidence: 87%
“…1 In study by Najar MS hemodialysis was given to 32.5%. 15 Total recovery of renal function found in 6/10 (60%), with complete recovery in 2/10 (20%) patients. The majority of remaining patients 4/10(40%) had partial recovery and did not require renal replacement therapy.…”
Section: Discussionmentioning
confidence: 96%